2018
DOI: 10.1016/j.vacuum.2017.12.038
|View full text |Cite
|
Sign up to set email alerts
|

X-ray tomography study on porosity in electron beam welded dissimilar copper–304SS joints

Abstract: Dissimilar joining of copper (C10300) to AISI-304 Stainless Steel (SS) sheets was performed using Electron Beam Welding (EBW) process. EBW was performed for two weld conditions such as with beam oscillation and without beam oscillation. X-ray Computed Tomography (XCT) technique was used for three-Dimensional (3D) visualization and quantification of porosity in the weld region. It was observed that the application of beam oscillation resulted in less porosity and the average pore size was found to be smaller as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…This is a typical application in sectors that produce high value-added components (aeronautics, aerospace, automotive and bioengineering, among others) in which an innovative improvement in quality control or in the assembly line can lead to savings of millions of dollars. In this regard, some projects have been carried out to study the most common defects, such as pores, residual stresses or cracks [14][15][16][17].…”
Section: Computed Tomography In Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a typical application in sectors that produce high value-added components (aeronautics, aerospace, automotive and bioengineering, among others) in which an innovative improvement in quality control or in the assembly line can lead to savings of millions of dollars. In this regard, some projects have been carried out to study the most common defects, such as pores, residual stresses or cracks [14][15][16][17].…”
Section: Computed Tomography In Metalsmentioning
confidence: 99%
“…Finally, it is also worth noting the possibilities provided by CT for the study of welding joints [14,28]. Welding is the most widely used procedure for connecting two metal parts.…”
Section: Computed Tomography In Metalsmentioning
confidence: 99%
“…Nomoto et al studied the porosity formation in various laser-welded samples using XCT technique and found that the tensile properties were greatly deteriorated by porosity in the welds [22]. Using XCT technique, Kar et al recently concluded that the application of beam oscillation reduced the porosity content in EB-welded copper-304stainless steel joints [23]. Similar decrease in porosity content with the application of beam oscillation is seen by Dinda et al in the EB welded steel -Fe Al alloy [17].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…No branch of engineering is alien to this technology, and almost any material has been studied using this technique, from metals or plastics to composites or rocks [5][6][7][8][9][10]. A detailed review of the state of the art in this field can be found in [11,12].…”
Section: Introductionmentioning
confidence: 99%